1998
DOI: 10.1677/jme.0.0210131
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of adrenocorticotrophin on the expression of the hamster steroidogenic acute regulatory protein

Abstract: In this study, we report the cDNA cloning of hamster adrenal steroidogenic acute regulatory (StAR) protein and the effect of adrenocorticotrophin (ACTH) on its expression in vivo. A hamster adrenal cDNA library was screened using an 852 bp fragment obtained by polymerase chain reaction; this fragment corresponds to the entire coding sequence (CDS) of the hamster adrenal StAR cDNA. Ten clones of different lengths were isolated and sequenced. The longest clone was 1564 bp and contained 34 bp in the 5 -untranslat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…10,41 In mammals, studies have demonstrated that changes in the adrenal expression of star results in increases in StAR protein. 43,44 The changes in star mRNA expression observed in this study reflect the pattern of whole-body cortisol, supporting the idea that StAR is an important component of the acute stress response in zebrafish. Moreover, the transient nature of the response suggests that the timing of sampling in relation to the stressor may be critical to defining the transcriptional contribution of star to the stress response.…”
Section: Discussionsupporting
confidence: 78%
“…10,41 In mammals, studies have demonstrated that changes in the adrenal expression of star results in increases in StAR protein. 43,44 The changes in star mRNA expression observed in this study reflect the pattern of whole-body cortisol, supporting the idea that StAR is an important component of the acute stress response in zebrafish. Moreover, the transient nature of the response suggests that the timing of sampling in relation to the stressor may be critical to defining the transcriptional contribution of star to the stress response.…”
Section: Discussionsupporting
confidence: 78%
“…?3 Moreover, it has been reported in the hamster that administration of ACTH induces a rapid increase in adrenal StAR mRNA and protein, thus further emphasizing the regulatory importance of ACTH in vivo. 33 We did not assess the expression of any steroidogenic enzymes in this study. It is quite probable the expression levels of some of these enzymes increased after ACTH exposure, and contributed to the increased output.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that ACTH administration [14,15] and sodium restriction [16] in vivo affected the formation of different species of StAR in rat [14,16,17] and hamster [14] adrenals.…”
Section: Introductionmentioning
confidence: 87%
“…Since the original report on the mouse StAR [1], StAR was cloned from 13 other animal species including the hamster [15]. By alignment analysis of the amino acid sequences of all these StARs, we have found conserved putative phosphorylation sites among most animal species.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation